Social and physical environment independently affect oviposition decisions in Drosophila. (22nd September 2021) - Churchill, Emily R; Dytham, Calvin; Bridle, Jon R; Thom, Michael D F
Abstract: In response to environmental stimuli, including variation in the presence of conspecifics, genotypes show highly plastic responses in behavioral and physiological traits influencing reproduction. Although extensively documented in males, such female responses are rather less studied. We expect females to be highly responsive to environmental variation and to differentially allocate resources to increase offspring fitness, given the major contribution of mothers to offspring number, size, and developmental conditions. Using Drosophila melanogaster, we (a) manipulate exposure to conspecific females, which mothers could use to anticipate the number of potential mates and larval density, and; (b) test how this interacts with the spatial distribution of potential oviposition sites, with females from higher densities expected to prefer clustered resources that can support a larger number of larvae. We found that high density females were slower to start copulating and reduced their copulation duration, the opposite effect to that observed in males. There was a parallel, perhaps related, effect on egg production: females previously housed in groups laid fewer eggs than those housed in solitude. Resource patchiness also influenced oviposition behavior: females preferred aggregated substrate, which attracted more females to lay eggs. However, we found no interaction between prior housing conditions and resource patchiness, indicating that females did not perceive the value of different resource distributions differently when exposed to environments that could signal expected levels of larval competition. We show that, although exposure to consexual competition changes copulatory behaviors of females, the distribution of oviposition resources has a greater effect on oviposition decisions. Abstract : When choosing how many eggs to produce, female fruit flies must consider the physical environment and the likely level of competition their offspring will face. Females raised with other females were slower to mate, mated for less time, and laid fewer eggs. However, when choosing where to lay, patchiness of laying sites had a greater impact than social environment: clustered resources attracted more females, who laid on more of the available patches.